2014
DOI: 10.18632/oncotarget.2101
|View full text |Cite
|
Sign up to set email alerts
|

NY-ESO-1 as a potential immunotherapeutic target in renal cell carcinoma

Abstract: Background: Novel immune therapies targeting tumor specific antigens are being developed. Our purpose was to determine expression of the cancer testes antigen NY-ESO-1 in renal cell carcinoma (RCC), as NY-ESO-1 targeting approaches, particularly adoptive cell therapy, have not been evaluated in this disease.Methods: We employed tissue microarrays containing >300 unique RCC cases and adjacent benign renal tissue to determine NY-ESO-1 expression using a quantitative immunofluorescence method. In addition, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…KY-CC-19/TSGA2 mRNA expression also increased at 7 times in tumor case N3 and at 10 times in tumor case N9, despite for colon cancer cases NN 1, 2, 4, 5, 8 its normal expression down regulated at 2-3.5 times (Figure, b). KY-CC-15/PLRG1 mRNA in addition to tumor case N7 have slightly increased expression at 3 times in tumor case N3 and near the same level of expression compare to normal colon in tumor cases NN 1,2,4,5,6,8,9 (difference range at 0.48-1.96) (Figure, c). KY-CC-15/PLRG1 and KY-CC-19/TSGA2 represent the genes with selective activation of normal expression in some cases of colon cancer and may be immunogenic as aberrantly expressed.…”
Section: Mrna Expression Profile Of Serologically Defined Colon Cancementioning
confidence: 88%
See 1 more Smart Citation
“…KY-CC-19/TSGA2 mRNA expression also increased at 7 times in tumor case N3 and at 10 times in tumor case N9, despite for colon cancer cases NN 1, 2, 4, 5, 8 its normal expression down regulated at 2-3.5 times (Figure, b). KY-CC-15/PLRG1 mRNA in addition to tumor case N7 have slightly increased expression at 3 times in tumor case N3 and near the same level of expression compare to normal colon in tumor cases NN 1,2,4,5,6,8,9 (difference range at 0.48-1.96) (Figure, c). KY-CC-15/PLRG1 and KY-CC-19/TSGA2 represent the genes with selective activation of normal expression in some cases of colon cancer and may be immunogenic as aberrantly expressed.…”
Section: Mrna Expression Profile Of Serologically Defined Colon Cancementioning
confidence: 88%
“…overexpressed or with activity in tumor cells (activated only in neoplastic cells and silence in normal cells, overexpressed in tumor cells, mutated genes), those can predict its possible association with tumorigenesis [6]. Several tumor-specific antigens such as NY-ESO-1, MAGE-1, MAGE-3, SSX2, Melan-A, and tyrosinase proteins are promising sensitive and specific target molecules for cancer screening and diagnosis, cancer immuno-therapy and development of antigen-specific cancer vaccines [7][8][9].…”
mentioning
confidence: 99%
“…NY-ESO-1 -это опухоль-ассоциированный белок, который ограниченно экспрессируется в нормальных тканях, но резко повышает уровень экспрессии в эпителиальных опухолях яичников и других солидных новообразованиях. Функция NY-ESO-1 до сих пор неизвестна, но предполагается, что он может участвовать в иммортализации, самообновлении, миграции [12]. Раково-тестикулярный антиген MAGE-A4 имеет высокий уровень экспрессии в метастазах солидных опухолей по сравнению с первичными опухолями, но отсутствует в большинстве нормальных тканей [13].…”
Section: Discussionunclassified
“…Elevated expression levels of NY-ESO-1 have been demonstrated in a proportion of RCC samples in another study with higher expressions observed in metastatic samples compared with the corresponding primary tumors. NY-ESO-1 expression has been considerably higher in primary RCC samples compared with adjacent normal renal tissues and in clear cell carcinomas compared with papillary RCC [17].…”
Section: Ctag1b (Ny-eso-1)mentioning
confidence: 94%